1988
DOI: 10.1302/0301-620x.70b1.3339056
|View full text |Cite
|
Sign up to set email alerts
|

Injuries of the acetabular triradiate cartilage and sacroiliac joint

Abstract: Four patients with injuries of the acetabular triradiate cartilage are presented. In three of them premature fusion of the cartilage occurred; two of these developed acetabular deformity and subluxation of the hip. In all patients the sacroiliacjoint also was injured; in two, thejoint was completely disrupted, leading to fusion and growth disturbance of the ilium. As injury ofthe triradiate cartilage is easily missed on the initial radiograph, it is advised that all patients with pelvic trauma should be follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 0 publications
0
31
0
1
Order By: Relevance
“…Complete or partial growth arrest of the triradiate cartilage may be seen after pelvic fractures [1,2,7,15,16,18], infection [4,20], or iatrogenic damage after pelvic osteotomy [13] .The consequences of physeal growth disturbance, shown by experimental [5,6] and clinical studies [1,2,15,16,18], include acetabular dysplasia and subluxation or dislocation of the femoral head. Conceptually, restoration of normal growth is the goal of treatment no matter the location of the physeal bar; in most locations, this is achieved surgically.…”
Section: Discussionmentioning
confidence: 99%
“…Complete or partial growth arrest of the triradiate cartilage may be seen after pelvic fractures [1,2,7,15,16,18], infection [4,20], or iatrogenic damage after pelvic osteotomy [13] .The consequences of physeal growth disturbance, shown by experimental [5,6] and clinical studies [1,2,15,16,18], include acetabular dysplasia and subluxation or dislocation of the femoral head. Conceptually, restoration of normal growth is the goal of treatment no matter the location of the physeal bar; in most locations, this is achieved surgically.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of the nonarticular triradiate medially (one third) and the cup-shaped articular acetabular cartilage laterally (two thirds). 2,3 The triradiate cartilage has been described as having three flanges. The first is anterior and superior, lying between the ilium and pubis.…”
Section: Anatomy and Growth Of The Acetabulummentioning
confidence: 99%
“…Acetabular development occurs by a combination of enchondral, interstitial, and appositional growth. [1][2][3][4] Acetabular development can be adversely affected by triradiate cartilage trauma. Injury to its blood supply can lead to premature physeal closure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pietrafesa and Hoffman demonstrated that 62e93% of hip dislocations result from motor vehicle crashes. 12 For bilateral posterior hip dislocation to happen it need both hip must be loaded while in attitude of flexion, a posterior dislocation is produced when the flexed knee strikes against the dashboard with the hip flexed and adducted. In u r n a l o f c l i n i c a l o r t h o p a e d i c s a n d t r a u m a 5 ( 2 0 1 4 ) 1 5 4 e1 5 6 our case child was fallen on ground from tractor seat located around the height of 8 feet on his knees over ground.…”
Section: 11mentioning
confidence: 99%